FORMING STUDENTS' KNOWLEDGE AND SKILLS BY CREATING PRACTICAL PROGRAMS IN THE PYTHON PROGRAMMING LANGUAGE - Menura Ashurova (European Science Publishing, 2024)
This article talks about the methods of forming and using students' knowledge and skills using the Python programming language, the use of practical programs in the educational process, and the types of practical programs.
Keywords: components, skill, layout, exhibition, technical means, components, competence.